The Influence of Jogjakarta Outer Ring Road Development Plan on the National Roads in the Special Region of Yogyakarta - Prima J. Romadhona; Affan Gaffarudin; Thareq I. Tanza; Arief R. Wiwaha (Journal of the Civil Engineering Forum, 2021)
The Influence of Jogjakarta Outer Ring Road Development Plan on the National Roads in the Special Region of Yogyakarta